To the public : Being informed that many of our fellow-citizens entertain apprehensions, that if we continue in this place, we may as usual carry on and transact trade and business ... we do therefore ... declare, that we will not transact any trade or commerce whatsoever . - Murray, Robert, 1721-1786 (LLMC-digital (Series), 1775)
Concerning the non-importation agreements.